Pelatihan Tata kelola Desa Wisata Halal Berbasis Media Branding Strategy di Desa Labuhan Jung Koneng Kabupaten Bangkalan - Dawam, Aulia; Rizkiyah, Ilham Zainia (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Promoting halal tourism destinations is one of the most important things to do, one of which is a tourist attraction in Labuhan Jung Koneng Village. Purpose This activity provides training on the use and creation of websites, accounts, and Instagram content to serve as media for promoting halal tourist destinations in Labuhan Jung Koneng Village, Bangkalan Regency. The event was attended by 20 people from the community around Labuhan village and managers of tourist sites. The method of implementing community service activities (PkM) uses lecture and discussion methods. The activity took place over three days, from February 24 to February 26, 2023. As a result of the PkM activities, training was carried out on the use and creation of websites and Instagram account content, which became a means of promoting halal tourist destinations in Labuhan Jung Koneng Village, Bangkalan Regency. It is hoped that it will become an effective and efficient means of promotion to display the tourist attraction of Labuhan Jung Koneng Village.